MODAL MANUSIA DAN PERTUMBUHAN EKONOMI (PERANAN KNOWLEDGE DAN PENELITIAN DALAM PERTUMBUHAN EKONOMI NEO KLASIK) - Wahyoedi, Soegeng (Manajemen Bisnis Kompetensi, 2014)
ABSTRACT Neo-classical economic growth saw determinant of economic growth from the supply side (supply), first, look at the human capital factors (human capital) as a determinant of economic growth. Two important things in human capital are education and health which believed to increase the knowledge (knowledge) and research (research), using the neoclassical growth model, economic growth is determined by labor, physical capital, and technology. By using a sample of 10 countries with the highest competitiveness version of the world economic and ASEAN countries found a positive relationship between the competitiveness of a country with a per capita income; positive relationship between education and competitiveness of a country; positive relationship between education and innovation, between education and income per capita, between research income per capitaÃÂ Keywords: Human Capital, Knowledge, Research, Economic Growth